Qualitative Risk Assessment on the transmission of HPAI (H5N1) virus from backyard and medium-scale commercial farms to household free-range poultry in Nigeria - Abdu, P. A. (International Food Policy Research Institute, 2010)
The Nigerian poultry industry, comprising both commercial and rural poultry systems, experienced the first highly pathogenic avian influenza (HPAI) H5N1 outbreak in 2006. This industry provides an affordable source of protein to millions of Nigerians through poultry eggs and meat. The rural poultry production system is essential in poverty alleviation, food security and the promotion of gender equity while meeting important social and cultural needs and obligations of Nigerians.